UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PEMELIHARAAN LISTRIK KENDARAAN RINGAN MENGGUNAKAN MEDIA ANIMASI SISWA KELAS XI TKR DI SMK TAMANSISWA NANGGULAN KULON PROGO TAHUN PELAJARAN 2015/2016 - Lilik Anton Susilo; Tarto Sentono (Jurnal Taman Vokasi, 2016)
The aim of this research is to improve the activity and the learning result of the XI grade students of Light Vehicle Engineering Program (TKR) in SMK Tamansiswa Nanggulan Kulon Progo in the Subjects of Electric Maintenance of Light Vehicle Using Animation Media. This research is a classroom action research, with research subjects, totaling 24 students. This research was conducted in three cycles, each cycle made of four phases, namely: Planning, Implementation of the action, Observations and Reflections. Data collection techniques in this study using observation sheet and test instruments.Â The research shows students' learning activeness of 54,75 % in the first cycle, increased in the second cycle into 72,62 % and then increased again to 86,29 % in the third cycle. The student learning outcomes reached 67,08 in the first cycle, increasing to 74,17 in the second cycle, and increased again to 83,33 in the third cycle. It can be concluded that the animation media can be used to improve the studentsâ€™ learning activity and learning results in the Subjects of Electric Maintenance of Light Vehicle for the XI grade students of Light Vehicle Engineering Program (TKR) in SMK Tamansiswa Nanggulan Kulonprogo.